Aerobic exercise abolishes cTBS-induced suppression of motor cortical excitability. (28th October 2016) - Singh, Amaya M.; Duncan, Robin E.; Staines, W. Richard
Highlights: It is unclear whether exercise can be used to enhance the induction of LTD in M1. Exercise abolishes cTBS-induced suppression at 30 min post-stimulation. Exercise may not be suitable to prime all types of experience-dependent plasticity. Exercise may favour the induction of LTP. Abstract: A preceding bout of acute aerobic exercise can enhance the induction of early long-term potentiation (LTP) in the primary motor cortex (M1). However, the influence of exercise when performed after the induction of plasticity has not been investigated. In addition, it is unclear whether the same effects are seen with techniques that induce long-term depression (LTD). We used continuous theta-burst stimulation (cTBS) to temporarily suppress cortical excitability and investigate whether moderate-intensity cycling exercise would alter the duration or intensity of cTBS after-effects in a nonexercised upper limb muscle. We observed that cTBS effects were abolished when followed by exercise, with no corresponding changes in intracortical network activity. We hypothesize that the induction of LTD may be suppressed by exercise-linked neurotransmitters that interact with glutamate receptors. Exercise appears to shift the neural balance towards facilitation and may work to counteract the effects of LTD-like processes.